2022
DOI: 10.3390/toxins14070460
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Bee Venom Components against Breast Cancer

Abstract: While the survival rate has increased due to treatments for breast cancer, the quality of life has decreased because of the side effects of chemotherapy. Various toxins are being developed as alternative breast cancer treatments, and bee venom is drawing attention as one of them. We analyzed the effect of bee venom and its components on breast cancer cells and reviewed the mechanism underlying the anticancer effects of bee venom. Data up to March 2022 were searched from PubMed, EMBASE, OASIS, KISS, and Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 42 publications
1
19
0
1
Order By: Relevance
“…El-Fiky et al (2022) found that the bioactive components of bee venom can be used as an alternative to improve humans' health. Kwon et al (2022) reported that BV has anti-breast cancer activity. El Naggar et al (2023) reported that BV is a promising Apitherapy for chronic toxoplasmosis markedly enhanced by loaded metal organic frameworks.…”
Section: Discussionmentioning
confidence: 99%
“…El-Fiky et al (2022) found that the bioactive components of bee venom can be used as an alternative to improve humans' health. Kwon et al (2022) reported that BV has anti-breast cancer activity. El Naggar et al (2023) reported that BV is a promising Apitherapy for chronic toxoplasmosis markedly enhanced by loaded metal organic frameworks.…”
Section: Discussionmentioning
confidence: 99%
“…Biomedical Application Peptide Surgical site infection (SSI) LL-37 [15], hBD2&3 [16], Protegrins [17], Histatins [18], Ranalexin [19], Pexiganan [20], Magainin [21], HNP1 [22] Contact lens-associated microbial keratitis (CLMK) α-MSH [23], Melimine [24], Pexiganan [25], Bacitracin [26], Dermcidin [27] Dental applications LL-37 [28], Dermaceptin [29], Nisin, Histatins [30], hBD1 [31], human beta-defensin-3 [32], human beta-defensin-5, Cateslytin [33], Myxinidin [34], HHC-36 [34] Bone-graft applications KLD [35], E14LKK [36] Tissue generation DermaceptinS4 [37], Thanatin [38], LLKKK18 [39], DPK-060 [40], SMAP-29 [41], G3KL [42], G3R, MSI-78 Anticancer agents pAntp [43], KT2 [44], RT2 [45], LL37 [46], LTX-315, [46] melittin [47]…”
Section: Sl Nomentioning
confidence: 99%
“…, ovarian, prostate, breast, lung by affecting cell cycle, proliferation/growth, motility, migration, through a complex mechanism implying different signal transduction and regulatory pathways. 27–30…”
Section: Introductionmentioning
confidence: 99%